Analisis Strategi Pembelajaran Fiqih dan SKI Dalam Mata Pelajaran PAI di SMP Plus Ja-Alhaq Kota Bengkulu: Tinjauan Pedagogis dan Praktis - Azidnia Fauza; Nurlaili; Dayun Riadi (Ameena Journal, 2026)
This analysis aims to examine the learning strategies for Fiqh (Islamic Jurisprudence) and Islamic Cultural History (ISCR) in Islamic Religious Education (PAI) at SMP Plus Ja-alHaq in Bengkulu City. Through a pedagogical analysis approach and practical review, this study identifies a paradigm shift from conventional memorization-based methods to a contextual, active, collaborative, and character-building-oriented approach. The analysis focused on the components of the approach, methods, media, assessment, and implementation challenges in the field. The results indicate that optimizing Fiqh learning requires a problem-based learning strategy (PBL) and hands-on practice, while ISCR requires a historical-critical and reflective approach through storytelling, role-play, mini-projects, and field studies. Integrating the two materials through integrated themes and Project-Based Learning (PJBL) is recommended to strengthen Islamic legal literacy and moderate Islamic identity. This study also presents a seven-component diagnostic analysis tool as an evaluation instrument for learning strategies. Practical implications include teacher training in 21st-century pedagogy, the development of integrated modules based on Bengkulu's local wisdom, and the implementation of authentic assessments in accordance with the Independent Curriculum. This article is expected to serve as a pedagogical reference and operational guide for teachers, supervisors, and Islamic education researchers in Bengkulu City.